Ocorrência de Astraptes talus (Cramer, 1777) (Lepidoptera: Hesperiidae) em Associação com Mucuna pruriens (Fabaceae) e seus Parasitóides (Hymenoptera) em Seropédica, RJ - Santos Resende, André Luis; Aguiar-Menezes, Elen Lima; Marinho Guerra, José Guilherme; Tavares, Marcelo Teixeira; Menezes, Eurípedes Barsanulfo (ENTOMOTROPICA, 2011)
This study reports Mucuna pruriens DC. as host plant of Astraptes talus (Cramer) in Seropedica, Rio de Janeiro, Brazil. It was recorded the primary parasitism by two species of Hymenoptera: one of the genus Apanteles Foerster (Braconidae) and Horismenus opsiphanis (Schrottky) (Eulophidae), and the hyperparasitism by Conura immaculata (Cresson) (Hymenoptera: Chalcididae).